2019
DOI: 10.1111/epi.16054
|View full text |Cite
|
Sign up to set email alerts
|

Dravet syndrome as part of the clinical and genetic spectrum of sodium channel epilepsies and encephalopathies

Abstract: Dravet syndrome is the most studied form of genetic epilepsy. It has now been clarified that the clinical spectrum of the syndrome does not have firmly established boundaries. The core phenotype is characterized by intractable, mainly clonic, seizures precipitated by increased body temperature with onset in the first year of life and subsequent appearance of multiple seizures types still precipitated by, but not confined to, hyperthermia. Cognitive impairment is invariably present when the full syndrome is man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 57 publications
0
56
0
7
Order By: Relevance
“…It is possible -and perhaps likely -that mice remaining alive represent a nonrandom subset of the initial population. It is well known that there is a spectrum of disease severity in Scn1a+/mice , similar to that observed in humans [Harkin et al, 2007, Mei et al, 2019, the basis of which is unclear but may involve genetic modifiers , Calhoun et al, 2017. This concern may pertain to any study involving an experimental animal model of a neurodevelopmental disorder associated with mortality.…”
Section: Introductionmentioning
confidence: 85%
“…It is possible -and perhaps likely -that mice remaining alive represent a nonrandom subset of the initial population. It is well known that there is a spectrum of disease severity in Scn1a+/mice , similar to that observed in humans [Harkin et al, 2007, Mei et al, 2019, the basis of which is unclear but may involve genetic modifiers , Calhoun et al, 2017. This concern may pertain to any study involving an experimental animal model of a neurodevelopmental disorder associated with mortality.…”
Section: Introductionmentioning
confidence: 85%
“…Over 150 mutations in the SCN1A gene have been described. Another form of epilepsy connected with SCN1A mutations, apart from DS, is epilepsy with febrile seizures plus and epilepsy of infancy with migrating focal seizures [ 1 , 2 , 3 , 4 ]. Familial hemiplegic migraine also may be caused by abnormalities within SCN1A gene [ 1 , 2 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 75–85% of individuals affected by DS have loss-of-function mutations in the SCN1A gene encoding the sodium channel alpha subunit [ 2 ]. In SCN1A mutation negative patients with clinical similarity to DS, different genetic background is found, particularly the following gene mutations: PCDH19 , CHD2 , STXBP1 , HCN1 , GABRG2 , GABRA1 , and SCN1B [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Precision medicine: novel treatment strategies developed from pathophysiological knowledge 3. Precision medicine: aetiology-based preventive treatments and in progress treatments Clinical-based evidence of known ASM modifying -either worsening or improving -seizure frequency One of the first and best example of how the identification of the underling genetic aetiology guides treatment is that of Dravet Syndrome (DS) the most renowned and studied developmental and epileptic encephalopathy (DEE) (Mei et al 2019). Well before the genetic cause was identified, some clinical reports indicated that sodium channel blockers including lamotrigine (LTG) and carbamazepine (CBZ) should be avoided in patients with DS since they have the potential to determine an increase in seizure frequency evolving to status epilepticus in some patients (Guerrini et al, 1998;de Lange et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Well before the genetic cause was identified, some clinical reports indicated that sodium channel blockers including lamotrigine (LTG) and carbamazepine (CBZ) should be avoided in patients with DS since they have the potential to determine an increase in seizure frequency evolving to status epilepticus in some patients (Guerrini et al, 1998;de Lange et al 2018). Following the discovery that DS is associated to mutations of the alpha1 subunit of the sodium channel (SCN1A) possibly causing loss of channel function, the clinical evidence that the administration of sodium channel blockers made seizure worse was partly explained (Claes et al 2001;Mantegazza, Marini 2010;Mei et al 2019). Although complete seizure control is rarely attainable, clinical studies have shown that the combination of valproic acid (VPA), clobazam (CLB) and stiripentol (STP) is the most effective in preventing seizures especially avoiding the evolution into status epilepticus, frequently observed in infants with DS (Ceulemans et al 2004;Wirrel et al 2018, Wirrel andNabbout 2019).…”
Section: Introductionmentioning
confidence: 99%